Preparation method and application of carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity

By using manganese nitrogen doped carbon dots prepared by sodium carboxymethylcellulose, the problems of high cost and non-renewable carbon sources in the existing carbon dot preparation are solved, and the accuracy and sensitivity of nitrite detection are improved through multi-mode detection.

CN119685009AActive Publication Date: 2025-03-25DALIAN POLYTECHNIC UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411831803.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

There are problems with high cost and non-renewable carbon sources in the existing carbon dot preparation process, and there are problems with inaccurate detection results caused by a single detection mode.

Method used

Manganese nitrogen doped carbon doped carbon dots with simulated oxidase activity and photoluminescence properties were prepared by hydrothermal method using natural renewable, inexpensive and easy-to-access sodium carboxymethylcellulose as carbon source, and used for colorimetric-ratio-fluorescence multi-mode detection of nitrite.

Benefits of technology

The preparation of low-cost, renewable carbon dots has been achieved, the scope of application of carbon dots in the fields of biomedical and sensors has been expanded, and the accuracy and sensitivity of nitrite detection have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185721340000071
    Figure BDA0005185721340000071
  • Figure HDA0005185721350000011
    Figure HDA0005185721350000011
  • Figure HDA0005185721350000012
    Figure HDA0005185721350000012
Patent Text Reader

Abstract

The invention relates to a preparation method and application of carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity, and belongs to the technical field of nano material preparation and nitrite detection. Sodium carboxymethyl cellulose, ethidene diamine and manganese chloride are dissolved in deionized water for hydrothermal reaction to prepare the carbon dots, the concentration of the sodium carboxymethyl cellulose is 0.04 g / mL, the mass ratio of the ethidene diamine to the sodium carboxymethyl cellulose is (0.5-1.5): 1, and the mass ratio of the manganese chloride to the sodium carboxymethyl cellulose is 1: 1. The manganese-nitrogen-carbon dots are prepared from the cellulose-based precursor, the raw materials and the process are green and environment-friendly, the cost is low, the equipment and the process are simple, and large-scale production is facilitated. The prepared manganese-nitrogen carbon dots have fluorescence and simulated oxidase activity at the same time, can realize colorimetric-ratio-fluorescence'multi-mode 'detection on nitrite, have the advantages of high sensitivity, high accuracy, strong anti-interference capability and the like, and are beneficial to expanding the application field of the carbon dots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity, belonging to the technical field of nano material preparation and nitrite detection. Background Art

[0002] Nanozymes have the advantages of high stability, low cost and adjustable enzyme activity. They can be used as substitutes for natural enzymes and have attracted widespread attention from researchers. At present, nanozymes mainly include metal organic frameworks, metal single atoms / diatoms, metal oxides and carbon materials. Among them, carbon dots are a low-dimensional carbon material with a size of less than 10nm, which has the advantages of easy preparation, low toxicity, biocompatibility and good dispersibility. In the reports of carbon dot nanozymes, researchers usually use structural design or heteroatom doping methods to give or improve the catalytic ability of carbon dots. In addition to mimicking enzyme activity, carbon dots also have excellent intrinsic photoluminescence ability. Therefore, the combination of photoluminescence characteristics and mimicking enzyme activity has opened up new ways for carbon dots in the biomedical field (antibacterial, anti-inflammatory and cancer treatment, etc.) and multimodal sensing.

[0003] At present, the research on carbon dots mimicking enzyme activity mainly focuses on mimicking peroxidase activity. Carbon dots (CDs) with mimicking peroxidase properties need to introduce unstable hydrogen peroxide during use, which may cause unexpected risks and errors. As another member of the nanozyme family, mimicking oxidase CDs can play a catalytic role in the presence of dissolved oxygen during use, so its use scenarios are more flexible and extensive. In related reports, researchers used small molecule carbon sources such as citric acid, serine, and ethylenediaminetetraacetic acid to prepare CDs with mimicking oxidase activity. However, small molecule carbon sources usually have problems such as non-renewable or high production and processing costs. At present, the demand for carbon neutrality and industrial production is stimulating researchers to seek renewable and low-cost materials to produce CDs. Lignocellulose-based biomass is a green and renewable natural resource, including cellulose, lignin and hemicellulose. It has the advantages of being renewable, abundant reserves and low cost. It is an ideal carbon source for industrial production of low-cost CDs. Lignin is a polymer composed of phenylpropane units with fewer active functional groups. CDs prepared with it as a raw material have very low quantum efficiency. Although hemicellulose has abundant active functional groups, its uneven structure makes it difficult to regulate and explore the properties of CDs prepared from it. In comparison, cellulose has a more uniform structure and abundant active sites, which is conducive to the preparation of CDs. So far, most studies on cellulose-based CDs have focused on the study of photoluminescence properties, which is relatively single. Therefore, it is necessary to develop a CDs that combines fluorescence properties with simulated oxidase activity to expand its application range.

[0004] Nitrite is a food additive commonly used to preserve meat products, which can inhibit the reproduction of microorganisms. However, nitrite will bind to hemoglobin in the blood and interfere with oxygen transport, which is particularly harmful to pregnant women and infants. In addition, nitrite can also react with amino acids in the stomach to produce carcinogens N-nitrosamines. Currently, commonly used detection methods include ion chromatography, capillary electrophoresis, gas phase chemiluminescence, and Griess reagent, but these methods often have problems such as high cost and complex operation. In addition, fluorescence detection and colorimetric ratiometry can also be used to detect nitrite. In recent years, some aromatic compounds containing primary amines, such as folic acid, neutral red, and anthocyanins, have been made into fluorescent materials that can detect nitrite. In addition, some materials with simulated oxidase activity, such as hollow MnFeO, CoMnO3 nanofibers, and Co-NC nanomaterials, are used to detect nitrite by ratiometric colorimetry. However, the above detection methods are all single detections, which are easily interfered by the environment (for example, in detection scenarios where the sample is colored or mixed with fluorescent substances), resulting in inaccurate detection results. Therefore, there is an urgent need to develop a biomass-based CDs that can simultaneously possess photoluminescence properties and simulate oxidase activity, and use it to construct a colorimetric-ratio-fluorescence "multimodal" sensing system to improve the accuracy of nitrite detection. Summary of the invention

[0005] In order to solve the technical problems existing in the existing carbon dot preparation process and the problem of inaccurate detection results caused by a single detection mode in the nitrite detection process, the present invention provides a method for preparing carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity and its application. The present invention uses natural, renewable, cheap and easily available sodium carboxymethyl cellulose (CMC) as a carbon source, ethylenediamine as a nitrogen dopant, and manganese chloride (MnCl2) as a manganese dopant, and prepares carbon dots with both photoluminescent properties and simulated oxidase activity by a simple, green and environmentally friendly hydrothermal method, and uses them for colorimetric-ratio-fluorescence "multi-mode" sensing detection of nitrite. The present invention has simple process, green environmental protection, simple equipment, and low cost of raw materials, which is conducive to large-scale industrial production.

[0006] A method for preparing carboxymethyl cellulose-based manganese-nitrogen doped carbon dots with simulated oxidase activity comprises dissolving sodium carboxymethyl cellulose, ethylenediamine and manganese chloride in deionized water, and performing a hydrothermal reaction to prepare the carbon dots.

[0007] In the method of the present invention, the concentration of the sodium carboxymethyl cellulose is 0.04 g / mL.

[0008] In the method of the present invention, the mass ratio of ethylenediamine to sodium carboxymethyl cellulose is 0.5-1.5:1.

[0009] Furthermore, when the mass ratio of ethylenediamine to sodium carboxymethyl cellulose increased from 0.5:1 to 1.5:1, the simulated oxidase activity of the carbon dots gradually increased; the fluorescence intensity increased significantly when the mass ratio of ethylenediamine to sodium carboxymethyl cellulose increased from 0.5:1 to 1:1, and decreased rapidly when it increased from 1:1 to 1.5:1.

[0010] Preferably, the mass ratio of ethylenediamine to sodium carboxymethyl cellulose is 1:1.

[0011] In the method of the present invention, the mass ratio of manganese chloride to sodium carboxymethyl cellulose is 1:1.

[0012] In the method of the present invention, the temperature of the hydrothermal reaction is 220° C. and the reaction time is 12 to 36 hours.

[0013] Preferably, the hydrothermal reaction time is 36 hours.

[0014] The present invention preferably has a technical solution comprising the following steps:

[0015] S1: Dissolve sodium carboxymethyl cellulose, ethylenediamine and manganese chloride in deionized water at room temperature, stir and mix well to obtain a transparent light yellow solution;

[0016] S2: The light yellow solution obtained in S1 was transferred to a high-pressure reactor, which was sealed and placed in a magnetic stirrer for hydrothermal reaction. After the reaction was completed, the mixture was cooled to room temperature to obtain a dark brown reaction solution.

[0017] S3: subjecting the reaction solution obtained in S2 to ultrasonic treatment, centrifugation and filtration, and dialyzing the filtered clear solution with deionized water to obtain a solid product;

[0018] S4: Drying the solid product obtained in S3 to obtain pure carbon dots.

[0019] In the method of the present invention, the ultrasonic condition is to ultrasonically disperse the cells in an ultrasonic cell crusher at a power of 100 W for 2 seconds and then stop for 3 seconds for 20 minutes.

[0020] In the method of the present invention, the centrifugation condition is centrifugation at 5000 rpm for 5 minutes.

[0021] In the method of the present invention, the filtering method is to use a 0.22 μm water filter membrane to filter out insoluble precipitates in the solution to obtain a clear solution.

[0022] In the method of the present invention, the dialysis condition is to purify the filtrate using a polycellulose ester dialysis bag with a molecular weight cutoff of 1000Da, the dialysis treatment time is 72h, and the water is changed every 8 to 12h.

[0023] In the method of the present invention, the drying condition is drying at 60° C. for 24 hours in a forced air drying oven.

[0024] Another object of the present invention is to provide carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots having simulated oxidase activity prepared by the above method.

[0025] Furthermore, the carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity are spherical nanoparticles with an average particle size of 3.5 to 4.2 nm.

[0026] Another object of the present invention is to provide the use of the above-mentioned carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity in nitrite detection.

[0027] Furthermore, the carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity can achieve multi-mode detection of nitrite through colorimetry, ratiometry and fluorescence methods.

[0028] A colorimetric-ratio-fluorescence multimodal detection method for nitrite based on carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity, in which an aqueous solution of carbon dots and an ethanol solution of 3,3',5,5'-tetramethylbenzidine are incubated for 2 minutes in an acetic acid-sodium acetate buffer solution at pH 4, and then a nitrite-containing solution is added and incubated for a further 15 minutes. The color change of the solution is observed, and the absorbance and fluorescence intensity are measured to achieve colorimetric-ratio-fluorescence multimodal detection of nitrite.

[0029] Furthermore, when the carbon dot aqueous solution is incubated with 3,3',5,5'-tetramethylbenzidine ethanol solution in an acetic acid-sodium acetate buffer solution at pH 4 and then a nitrite-containing solution is added and the incubation is continued, the color, absorbance and fluorescence intensity of the solution may change simultaneously, and nitrite may be detected by colorimetry, ratiometry and fluorescence methods simultaneously.

[0030] In the above technical solution, the volume ratio of the carbon dot solution, 3,3',5,5'-tetramethylbenzidine ethanol solution, acetic acid-sodium acetate buffer solution and nitrite solution is 1:2:115:2.

[0031] Furthermore, the concentration of the carbon dot aqueous solution is 1 mg / mL, and the concentration of the 3,3',5,5'-tetramethylbenzidine ethanol solution is 5 mM.

[0032] Furthermore, the detection range of the colorimetric method is 0 to 300 μM, and the color gradually changes from blue to green and then to yellow as the concentration of nitrite increases.

[0033] Furthermore, the detection range of the ratiometric method is 0 to 200 μM, and the detection limit is 3.50 μM.

[0034] Furthermore, the detection range of the fluorescence method is 0 to 100 μM, and the detection limit is 1.06 μM.

[0035] The carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity of the present invention have simulated oxidase activity, can reduce dissolved oxygen to superoxide anion free radicals, and superoxide anion free radicals can oxidize 3,3',5,5'-tetramethylbenzidine (TMB) to TMB + , the solution turns blue and absorbs at 652nm wavelength of visible light, then the oxidized TMB + It can undergo diazotization reaction with nitrite to change the solution from blue to green. As the concentration of nitrite increases, it gradually changes from green to yellow, thus achieving visual detection of nitrite. + The diazotization product generated with nitrite has an absorbance at 445nm, and the ratio of the absorbance at 652nm to that at 445nm (A652 / A445) is linearly related to the concentration of nitrite; TMB + The diazotization product generated by nitrite can quench the fluorescence of carbon dots, and the fluorescence intensity is linearly related to the concentration of nitrite.

[0036] Beneficial effects of the present invention:

[0037] (1) The present invention uses sodium carboxymethyl cellulose, a cellulose modification product with abundant reserves in nature, renewable, green and pollution-free, and low cost, as a carbon source to prepare carbon dots, thereby avoiding the problem that the carbon source material is expensive and difficult to obtain. At the same time, the present invention uses a simple and convenient one-step hydrothermal method to prepare carbon dots with both simulated oxidase activity and fluorescence properties. The raw material cost of the present invention is low and widely available, and the preparation method is simple to operate, economical and environmentally friendly, which is conducive to the industrial large-scale production of carbon dots.

[0038] (2) The present invention uses biomass as a carbon source to prepare carbon dots with simulated oxidase activity, which opens up new avenues for the high-value application of cellulose and also provides a new, low-cost raw material for the development of carbon dot nanozymes.

[0039] (3) The carbon dots prepared by the present invention having both simulated oxidase activity and fluorescence properties exhibited excellent TMB catalytic performance, with a maximum reaction rate (V max ) is 19.8×10 -5 mM s -1, the Michaelis constant (Km) is 0.159mM. The carbon dots prepared by the present invention can realize colorimetric-ratio-fluorescence multi-mode detection of nitrite, and the detection effect is sensitive. The detection range of the colorimetric method is 0-300μM; the detection range of the ratio method is 0-200μM, and the detection limit is 3.50μM; the detection range of the fluorescence method is 0-100μM, and the detection limit is 1.06μM.

[0040] (4) The carbon dots prepared by the present invention have abundant functional groups such as carboxyl, hydroxyl, and amino groups on their surfaces, good water solubility and dispersibility, and good biocompatibility. The sensing system constructed based on the carbon dots (a solution system consisting of carbon dots, TMB, and a buffer solution) can be used to detect a variety of substances such as nitrite, glutathione, and dopamine. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 (a) and (b) the transmission electron microscopy image of the carbon dots obtained in Example 1.

[0042] Figure 2 The fluorescence emission spectra of the carbon dots obtained in Example 5 at different excitation wavelengths (a) and in different pH environments (b).

[0043] Figure 3 This is the EPR spectrum of the carbon dots obtained in Example 5.

[0044] Figure 4 The results of the detection of nitrite by the carbon dots obtained in Example 5, wherein (a) is the UV-visible absorption spectrum of the carbon dots + TMB system in response to different concentrations of nitrite; (b) is the linear relationship between the A652 / A445 value and the nitrite concentration; (c) is the fluorescence spectrum of the carbon dots + TMB system in response to different concentrations of nitrite; (d) is the linear relationship between the F0 / F value and the nitrite concentration; (e) is the anti-interference ability test of the carbon dots + TMB system in detecting nitrite using the ratio method; (f) is the anti-interference ability test of the carbon dots + TMB system in detecting nitrite using the fluorescence method.

[0045] Figure 5 This is a diagram showing the effect of visual detection of nitrite by carbon dots obtained in Example 5. DETAILED DESCRIPTION

[0046] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0047] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0048] Example 1

[0049] A method for preparing carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity comprises the following steps:

[0050] 2 g of sodium carboxymethyl cellulose, 2 g of ethylenediamine (the mass ratio of ethylenediamine to sodium carboxymethyl cellulose is 1:1) and 2 g of manganese chloride are added to a beaker containing 40 mL of ultrapure water, stirred with a magnetic stirrer until mixed evenly, and then transferred to a 100 mL para-polyphenylene (PPL) liner; after the liner is sealed with a stainless steel reactor, it is heated with a magnetic stirrer equipped with a heating module, the hydrothermal reaction temperature is 220 ° C, and the reaction time is 24 h; after the reaction is completed, wait for the reactor to cool to room temperature, and the obtained dark brown The reaction solution was ultrasonically dispersed for 20 minutes by an ultrasonic cell disruptor under the conditions of 100W ultrasonic dispersion for 2 seconds and stop for 3 seconds, and then the solution was transferred to a 50mL centrifuge tube and centrifuged at 5000rpm for 10 minutes; the supernatant after centrifugation was collected and filtered with a 0.22μm pinhole water filter membrane, and then the filtrate was injected into a 1000Da dialysis bag for purification. The purification time was 72 hours, and the water was changed every 8 to 12 hours. Finally, the dialyzed solution was placed in a forced air drying oven to dry, and pure carbon dots were obtained.

[0051] The carbon dots obtained above were prepared into a carbon dot aqueous solution with a concentration of 1 mg / mL using deionized water. 25 μL of the carbon dot aqueous solution and 50 μL of 3,3',5,5'-tetramethylbenzidine ethanol solution (concentration of 5 mM) were added to 2875 μL of acetic acid-sodium acetate (pH = 4) buffer solution and incubated for 2 minutes. The absorbance of the mixed solution after incubation at 652 nm was 0.28. Among them, the absorbance value reflects the strength of the carbon dot simulated oxidase activity.

[0052] Example 2

[0053] Reference Example 1 is different from Example 1 in that the mass ratio of ethylenediamine to sodium carboxymethylcellulose is 0.5: 1. After the carbon dots prepared under this condition are incubated with TMB ethanol solution for 2 minutes, the absorbance at 652 nm is 0.03.

[0054] Example 3

[0055] Reference Example 1 is different from Example 1 in that the mass ratio of ethylenediamine to sodium carboxymethylcellulose is 1.5: 1. After the carbon dots prepared under this condition were incubated with TMB ethanol solution for 2 minutes, the absorbance at 652 nm was 0.38.

[0056] Example 4

[0057] Referring to Example 1, the difference from Example 1 is that the hydrothermal reaction time is 12 hours. After the carbon dots prepared under this condition are incubated with TMB ethanol solution for 2 minutes, the absorbance at 652 nm is 0.2.

[0058] Example 5

[0059] Referring to Example 1, the difference from Example 1 is that the hydrothermal reaction time is 36 hours. After the carbon dots prepared under this condition are incubated with TMB ethanol solution for 2 minutes, the absorbance at 652 nm is 0.62.

[0060] Result analysis:

[0061] Figure 1 The transmission electron microscope image and particle size distribution diagram of the carbon dots obtained in Example 1 show that the carbon dots are spherical nanoparticles with an average particle size of about 4 nm.

[0062] Figure 2 The fluorescence emission spectra of the carbon dots obtained in Example 5 under different concentrations (a) and excitation wavelengths (b). Figure 2 As can be seen from (a), the fluorescence intensity increases with the increase of carbon dot concentration. When the concentration is 0.12 mg / mL, it has the maximum fluorescence intensity. When the concentration exceeds 0.12 mg / mL, the fluorescence intensity gradually decreases due to the aggregation quenching effect. Figure 2 It can be seen from (b) that the fluorescence of the carbon dots has an excitation-dependent behavior. As the excitation wavelength changes, the fluorescence emission wavelength also changes accordingly.

[0063] Figure 3 The EPR spectrum of the carbon dots obtained in Example 5. During the test, DMPO was used as a scavenger for superoxide anion free radicals. When the carbon dots were not introduced, DMPO did not capture the free radicals. When the carbon dots were introduced, typical signals corresponding to the superoxide anion free radicals appeared, indicating that the principle of the carbon dots catalyzing the color change of TMB is to convert dissolved oxygen into superoxide anion free radicals, and then the free radicals robbed TMB of its electrons to oxidize and turn it blue.

[0064] Table 1 shows the raw materials, application conditions, maximum catalytic rate (V) of the carbon dots obtained in Example 5 and other carbon dots with simulated oxidase activity. max ) and substrate affinity (K m ) and other aspects. The carbon dots with simulated oxidase activity can be divided into two types, among which type one is metal-doped carbon dots and type two is metal-undoped carbon dots, the latter of which requires ultraviolet light or visible light activation to enable the carbon dots to produce oxidase-like activity. V of the carbon dots obtained in Example 5 of the present invention max Much higher than the carbon dots described in type II, and no photoexcitation is required for use; the V maxCompared with the type 1 carbon dots, it still has an advantage. m The K value is lower than that of all reported carbon dots. m The values ​​of (0.168-3.040) indicate that the carbon dots obtained in Example 5 have excellent affinity with TMB. In addition, the carbon dots obtained in Example 5 use renewable biomass as the carbon source, which is more economical and sustainable than other carbon dots with simulated oxidase activity.

[0065] Table 1 Comparison of raw materials, application conditions, maximum catalytic rate (Vmax) and substrate affinity (K) of Example 5 with other carbon dots with simulated oxidase activity in the prior art m ) and other aspects

[0066] in,

[0067] Literature [1]: Y.Zhang, M.Zhang, Y.Ma,

[0068] Literature [2]: X.Li, S.Ding, Z.Lyu, P.Tieu, M.Wang, Z.Feng, X.Pan, Y.Zhou,

[0069] Reference [3]: L. Wang, Y. Chen, Y. Ji, S. Zheng, F. Wang, C. Li, Cheap and portable paper chip with terrific oxidase-like activity and SERS enhancement performance for SERS-colorimetric bimodal detection of intracellular glutathione, Biosens. Bioelectron. 244 (2024) 115817.

[0070] Reference [4]: G. Wu, H. Qiu, C. Du, Z. Zheng, Q. Liu, Z. Wang, P. Luo, Y. Shen, Intelligent onsite dual-modal assay based on oxidase-like fluorescence carbon dots-driven competitive effect for ethyl carbamate detection, J. Hazard. Mater. 474 (2024) 134707.

[0071] Reference [5]: J. Li, Y. Zhou, Y. Xiao, S. Cai, C. Huang, S. Guo, Y. Sun, R. Bin Song, Z. Li, Carbon dots as light-responsive oxidase-like nanozyme for colorimetric detection of total antioxidant capacity in fruits, Food Chem. 405 (2023) 134749.

[0072] Reference [6]: Z. Jia, Y. Liu, L. Cheng, Z. Deng, M. Zhang, H. Tuo, Carbon dots with light-responsive oxidase-like activity for colorimetric detection of dopamine and the catalytic mechanism, Front. Chem. 11 (2023) 1–11.

[0073] Literature[7]:

[0074] Figure 4 This is a diagram showing the effect of the carbon dots obtained in Example 5 on nitrite detection using a sensing system constructed with the assistance of TMB. The construction method is as follows: the carbon dots are prepared with deionized water to form a carbon dot aqueous solution with a concentration of 1 mg / mL. 25 μL of the carbon dot solution and 50 μL of 3,3',5,5'-tetramethylbenzidine ethanol solution (concentration of 5 mM) are added to 2875 μL of acetic acid-sodium acetate (pH=4) buffer solution and incubated for 2 minutes. 50 μL of sodium nitrite solution of different concentrations are added and incubated for another 15 minutes. The color change is observed, and then the obtained solution is tested for fluorescence intensity using a fluorescence spectrophotometer and for absorbance using a UV-visible spectrophotometer. Figure 4 As can be seen in (a), when the nitrite concentration increases, the absorbance of the carbon dots + TMB system at 445 nm increases rapidly, and the absorbance at 652 nm decreases slightly. Figure 4 (b) shows that the absorbance ratio at 652 nm and 445 nm is linearly related to the concentration of nitrite, and the calculated detection limit is 3.50 μM. Figure 4 It can be seen from (c) that as the concentration of nitrite increases, the fluorescence intensity of the carbon dots + TMB system gradually decreases. Figure 4 (d) shows that the fluorescence intensity of the detection system is linearly related to the concentration of nitrite, and the calculated detection limit is 1.06 μM. In addition, Figure 4 (e) and Figure 4 (f) The carbon dots + TMB detection system has excellent anti-interference ability for both the ratio method and fluorescence method of nitrite ions.

[0075] Figure 5 The carbon dots obtained in Example 5 were incubated with TMB ethanol solution for 2 min, and the solution color changed after different concentrations of nitrite were introduced, thereby realizing the visual detection of nitrite. Figure 5 It can be seen that as the concentration of nitrite increases, the color of the detection system gradually changes from blue to green and finally to yellow, and the detection range is 0-300 μM.

Claims

1. A method for preparing carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity, characterized in that: Sodium carboxymethyl cellulose, ethylenediamine and manganese chloride are dissolved in deionized water and subjected to hydrothermal reaction to prepare carbon dots, wherein: The concentration of the sodium carboxymethyl cellulose is 0.04 g / mL, the mass ratio of ethylenediamine to sodium carboxymethyl cellulose is 0.5-1.5:1, and the mass ratio of manganese chloride to sodium carboxymethyl cellulose is 1:

1.

2. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 220° C., and the reaction time is 12 to 36 hours.

3. The preparation method according to claim 1, characterized in that: The steps include: S1: Dissolve sodium carboxymethyl cellulose, ethylenediamine and manganese chloride in deionized water at room temperature, stir and mix well to obtain a transparent light yellow solution; S2: The light yellow solution obtained in S1 was transferred to a high-pressure reactor, which was sealed and placed in a magnetic stirrer for hydrothermal reaction. After the reaction was completed, the mixture was cooled to room temperature to obtain a dark brown reaction solution. S3: subjecting the reaction solution obtained in S2 to ultrasonic treatment, centrifugation and filtration, and dialyzing the filtered clear solution with deionized water to obtain a solid product; S4: Drying the solid product obtained in S3 to obtain pure carbon dots.

4. Carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity prepared by the method according to any one of claims 1 to 3.

5. The carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity according to claim 4, characterized in that: The carbon dots are spherical nanoparticles with an average particle size of 3.5 to 4.2 nm.

6. Use of the carboxymethyl cellulose-based manganese-nitrogen doped carbon dots with simulated oxidase activity as claimed in claim 4 in nitrite detection.

7. The use according to claim 6, characterized in that: The carboxymethyl cellulose-based manganese-nitrogen-doped carbon dots with simulated oxidase activity can simultaneously realize multi-mode detection of nitrite through colorimetry, ratiometry and fluorescence.

8. A colorimetric-ratio-fluorescence multimodal detection method for nitrite based on carboxymethylcellulose-based manganese-nitrogen doped carbon dots with simulated oxidase activity, characterized in that: The carbon dot aqueous solution was incubated with 3,3',5,5'-tetramethylbenzidine ethanol solution in an acetic acid-sodium acetate buffer solution at pH 4 for 2 min, and then a nitrite-containing solution was added and incubated for a further 15 min. The color change of the solution was observed, and the absorbance and fluorescence intensity were measured to achieve colorimetric-ratio-fluorescence multimodal detection of nitrite.

9. The detection method according to claim 8, characterized in that: The volume ratio of the carbon dot solution, 3,3',5,5'-tetramethylbenzidine solution, acetic acid-sodium acetate buffer solution and nitrite solution is 1:2:115:2, wherein the concentration of the carbon dot aqueous solution is 1 mg / mL, and the concentration of the 3,3',5,5'-tetramethylbenzidine ethanol solution is 5 mM.

10. The use according to any one of claims 6 to 9, characterized in that: The detection range of the colorimetric method is 0-300 μM, and the color gradually changes from blue to green and then to yellow as the nitrite concentration increases; the detection range of the ratio method is 0-200 μM, and the detection limit is 3.50 μM; the detection range of the fluorescence method is 0-100 μM, and the detection limit is 1.06 μM.

Citation Information

Patent Citations

  • Nitrogen doped fluorescent carbon quantum dot and preparation method thereof

    CN108456519A

  • Preparation method of biomass nitrogen-doped carbon dots and product and application thereof

    CN110016338A

  • Preparation method and application of cellulose-based fluorescent functional material containing manganese complex

    CN114921241A

  • Yellow-green cellulose-based carbon quantum dot, preparation method and application of yellow-green cellulose-based carbon quantum dot in detection of chromium (VI) and ascorbic acid

    CN116023940A

  • Method for detecting glutathione based on Mn-CDs nano-enzyme colorimetric sensing technology

    CN119044085A